Investigating the impact of peatland degradation: A lipid biomarker analysis - Nasreen Jeelani; Katharina Fischer; Carrie L. Thomas; Klaus-Holger Knorr; Mariusz Lamentowicz; Mariusz Gałka; Stephan Glatzel (iScience, 2025)
Summary: Lipids, such as aliphatics, phenolics, and carboxylic acids, are key biomarkers for analyzing peat composition, decomposition, and microbial activity. This study provides a comparative analysis of lipid biomarkers from natural, extracted, degraded, and restored bog sites in Germany, Poland, and Austria. We investigate samples from various depths, assessing how effectively these biomarkers reflect environmental conditions and restoration success. The aliphatic hydrocarbon fractions showed the site specific pattern in n-alkanes (C15 to C33), with variations in carbon preference index (CPI), average chain length (ACL), and proxy of aquatic macrophytes input (Paq) indicating shifts in vegetation and moisture. The presence of triterpenoids, sterols, hopanoids, and archaeol provides insights into the vegetation composition and microbial processes. Our finding highlights the complex interaction of chemical and biological factors in peatlands. Restoration sites exhibit elevated biomarker concentrations similar to natural conditions, whereas degraded sites show lower concentrations, suggests additional restoration efforts are needed to achieve natural condition.